2006
DOI: 10.1007/s11883-006-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral cardiology: Recognizing and addressing the profound impact of psychosocial stress on cardiovascular health

Abstract: Psychosocial stress exerts independent adverse effects on cardiovascular health. The recent INTERHEART study reported that psychosocial stress accounted for approximately 30% of the attributable risk of acute myocardial infarction. Prospective studies consistently indicate that hostility, depression, and anxiety are all related to increased risk of coronary heart disease and cardiovascular death. A sense of hopelessness, in particular, appears to be strongly correlated with adverse cardiovascular outcomes. Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 63 publications
2
35
0
6
Order By: Relevance
“…In fact, it has been suggested that the magnitude of this depressive effect is similar to that of traditional cardiac risk factors such as hypertension and dyslipidemia (Das & O'Keefe, 2006).…”
mentioning
confidence: 99%
“…In fact, it has been suggested that the magnitude of this depressive effect is similar to that of traditional cardiac risk factors such as hypertension and dyslipidemia (Das & O'Keefe, 2006).…”
mentioning
confidence: 99%
“…Das et al recently reported findings from the Interheart study, which showed that psychosocial stress was responsible for <30% of the attributable risk of acute myocardial infarction. 2 In particular, a sense of hopelessness appeared to be strongly correlated with adverse cardiovascular outcomes. Similarly, Yusuf et al found that psychosocial factors represented the third greatest risk factor for acute myocardial infarction, after smoking and elevated ApoB/ApoA1 ratios.…”
Section: Epidemiology and Consequences Of Depressionmentioning
confidence: 98%
“…En ce qui a trait aux MCV, différentes études ont été conduites s'intéressant généralement aux traits de personnalité des patients coronariens ainsi qu'à leur niveau de stress (Das & O'Keefe, 2006;Haynes, Feinleib, & Kannel, 1980;Herrmann-Lingen & Buss, 2007;Jordan & Bardé, 2007;Molinari, Compare, & Parati, 2006;Myrtek, 2006;Ragland & Brand, 1988;Rozanski, Blumenthal, & Kaplan, 1999;Sparagon et al, 2001). Une étude longitudinale menée en Allemagne auprès de 5114 participants a conclu qu'un locus interne en ce qui concernait le contrôle de la maladie était associé à une diminution du risque d'infarctus du myocarde alors que les autres facteurs de personnalité mesurés n'ont pas été significativement associés à l'infarctus du 16 myocarde et aux AVC (Stiirmer, Hasselbach, & Amelang, 2006).…”
Section: Facteurs De Risque Et De Protectionunclassified
“…Toutefois, l'étiologie de la maladie coronarienne s'imprègne depuis peu de déterminants psychologiques (Das & O'Keefe, 2006;Haynes, Feinleib, & Kannel, 1980;HerrmannLingen & Buss, 2007;Jordan & Bardé, 2007;Molinari, Compare, & Parati, 2006;Myrtek, 2006;Ragland & Brand, 1988;Rozanski, Blumenthal, & Kaplan, 1999;Sparagon et al, 2001). Néanmoins, peu d'études sont menées afin de déterminer si les …”
Section: Introductionunclassified